Optical distortion compensation in the visual measurement with the new Depth From Defocus method - Sulej, Wojciech; Murawski, Krzysztof; Pustelny, Tadeusz (Photonics Letters of Poland, 2017)
The paper presents new approach to compensation the inaccuracy of shape mapping of the flaccid membrane used in the extracorporeal pneumatic heart assist pump. The original shape of the membrane was determined using specially developed DFD type method. The major problems affecting the inaccuracy of mapping the membrane result from the phenomenon of optical distortion. The invented approach to compensate for optical distortion in the process of visual measurement as well as the results obtained were presented. Full Text: PDF References K. Murawski, Method of measuring the distance using one camera, Patent Application No P.408076 (2014) - in Polish. DirectLink K. Murawski, M. Murawska, T. Pustelny, The system and method of determining the shape of the membrane pneumatic pump of extracorporeal heart assist device, Patent Application No P.414104 (2015) - in Polish. DirectLink M. Gawlikowski, T. Pustelny, R. Kustosz, "The physical parameters estimation of physiologically worked heart prosthesis", Journal de Physique IV France 137, 73 (2006). CrossRef K. Murawski, "Measurement of Membrane Displacement Using a Motionless Camera", Acta Phys. Pol. A 128(1), 10 (2015). CrossRef K. Murawski, "Measurement of Membrane Displacement with a Motionless Camera Equipped with a Fixed Focus Lens", Metrology and Measurement Systems 22(1), 69 (2015). CrossRef K. Murawski, A. Arciuch, T. Pustelny, "Study of distance range visual measurement in the new Depth From Defocus method", Phot. Lett. Poland 8, 2 (2016). CrossRef L. Grad, K. Murawski, W. Sulej, "Research to improve the accuracy of determining the stroke volume of an artificial ventricle using the wavelet transform", Proc. SPIE 10455, 1045509 (2017). CrossRef W. Sulej, K. Murawski, "The membrane shape mapping of the artificial ventricle in the actual dimensions", Proc. FedCSIS ACSIS 11, 675 (2017). CrossRef W. Sulej, L. Grad, K. Murawski, "The technique of accuracy measurement of membrane shape mapping of an artificial ventricle", Proc. SPIE 10455, 104550B (2017). CrossRef